Consensus on the treatment of autoimmune bullous dermatoses: bullous pemphigoid, mucous membrane pemphigoid and epidermolysis bullosa acquisita - Brazilian Society of Dermatology - Claudia Giuli Santi; Alexandre Carlos Gripp; Ana Maria Roselino; Danielle Santana Mello; Juliana Olivieri Gordilho; Paula Figueiredo de Marsillac; Adriana Maria Porro (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Bullous pemphigoid, mucous membrane pemphigoid and epidermolysis bullosa acquisita are subepidermal autoimmune blistering diseases whose antigenic target is located at the basement membrane zone. Mucous membrane pemphigoid and epidermolysis bullosa acquisita can evolve with cicatricial mucosal involvement, leading to respiratory, ocular and/or digestive sequelae with important morbidity. For each of these dermatoses, a literature review covering all therapeutic options was performed. A flowchart, based on the experience and joint discussion among the authors of this consensus, was constructed to provide treatment orientation for these diseases in Brazil. In summary, in the localized, low-risk or non-severe forms, drugs that have immunomodulatory action such as dapsone, doxycycline among others may be a therapeutic option. Topical treatment with corticosteroids or immunomodulators may also be used. Systemic corticosteroid therapy continues to be the treatment of choice for severe forms, especially those involving ocular, laryngeal-pharyngeal and/or esophageal mucosal involvement, as may occur in mucous membrane pemphigoid and epidermolysis bullosa acquisita. Several immunosuppressants are used as adjuvant alternatives. In severe and recalcitrant cases, intravenous immunoglobulin is an alternative that, while expensive, may be used. Immunobiological drugs such as rituximab are promising drugs in this area. Omalizumab has been used in bullous pemphigoid.